PENGARUH JENIS MULSA DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAHE MERAH (Zingiber officinale Roscoe) - Muhammad Jalil; Irvan Subandar; Nurkiswa Nurkiswa (Jurnal Agrotek Lestari, 2018)
This research aims to know the effect of mulch and NPK dose towards growth and production of red ginger and the interaction of both factors. This research used Randomized Block Design (RBD) with three replications, the first factor is kinds of mulch that consist of three levels: without mulch, straw mulch, and spadix palm mulch. The second factor is dose of NPK fertilizer that consist of three levels: 75, 100 and 125kg/Ha. This research was conducted at experimental farm, Faculty of Agriculture Teuku Umar University, Meulaboh West Aceh, from 4 February until June 2013. The research showed that kind of mulch influenced significantly on plant height, aged 90 and 120 after planting. The number of tillers/plant aged of 30 after planting, significant effect on plant height, aged 60 after planting, heavy of  rhizomes and production per hectare, but the effect was not significant on high plant, aged 30 after planting and the number of tillers aged 60, 90 and 120 after planting. The best Growth and production of red ginger found in spadix palm mulching and straw mulching. Dose of NPK fertilizer significantly affected the rhizome weight per clump and production per hectare, but was not significant on high plant, number of tillers/plant aged 30, 60, 90 and 120 after planting. The best production of ginger found in NPK dose of 125 kg/Ha. There was no significant interaction between mulch and NPK treatment against any observed variables. Keywords: dose of NPK, growth, mulch, red ginger